Rhinosporidiosis presenting as an orbital mass (Journal of Pathology of Nepal, 2021)
Rhinosporidiosis is a chronic granulomatous disease. Diagnosis is made on the clinical presentation of the patient and confirmed by histopathological findings. We report a case of atypical rhinosporidiosis presenting as orbital mass and mimicked carcinoma. Hence the possibility of rhinosporidiosis should be excluded in the biopsy specimen of the orbital region especially for a patient from rural endemic areas.